Simultaneous reconstruction and segmentation algorithm for positron emission tomography and transmission tomography - Van de Sompel, D; Brady, M; IEEE (2008)
We present a new reconstruction algorithm for emission and transmission tomography. The algorithm performs maximum likelihood reconstruction and doubly stochastic segmentation simultaneously. The resulting reconstructions show promising edge-preservation as well as suppression of measurement noise. ©2008 IEEE.